Volume of mural thrombus plays a role in the elevation of inflammatory markers after endovascular aortic repair - Lee, Jae Hang; Choi, Jin-Ho; Kim, Eung-Joong (Journal of cardiothoracic surgery, 2018)
Although systemic inflammatory responses are common after endovascular aortic repair (EVAR), its etiology remains uncertain. It is normally well tolerated and has a benign course. This study was undertaken to investigate the possible etiology of post-EVAR inflammation by measuring volumes of chronic mural thrombus and fresh thrombus. The subjects of this study included 34 patients who underwent EVAR from February 2012 to July 2017. Inflammatory markers in all the patients were evaluated before surgery, using the highest value among the laboratory data up to 5 days after surgery, and postoperative computed tomographic angiography (CTA) was taken for all of them before their discharging. Volumes of mural thrombus and fresh thrombus were calculated by CTA. The mean interval from surgery to immediate postoperative CTA was estimated as 6.8 ± 4.0 days. After undergoing EVAR, white blood cell (WBC) (p < 0.01), C-reactive protein (CRP) (p < 0.01) and erythrocyte sedimentation rate (ESR) (p = 0.01) were significantly elevated. Two groups were defined according to the post-implantation syndrome (PIS) by the criteria of systemic inflammatory response syndrome (SIRS);no significant differences were observed in any factors between the two groups. Classification of two groups by the criteria of increasing WBC and CRP revealed that inflammatory markers were significantly enhanced as the volume of mural thrombus increased (p = 0.03). However, no significant risk factor was found in view of aneurysmal growth after EVAR. Volume of mural thrombus is an important risk factor for the elevation of inflammatory markers after EVAR.